PERAN PEREMPUAN DALAM PEMBANGUNAN EKONOMI DAN PENGUATAN KESETARAAN GENDER - Rosyidi, Laily; Rofiq, Aunur; Khusnudin (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
Women play an important role in economic development and the promotion of gender equality, as highlighted in various research papers. Women's empowerment is essential for socio-economic progress, emphasizing the need for women to have control over resources and decision-making capacity. Women entrepreneurs are key drivers of social change and gender equality, challenging norms and contributing to economic growth. Using the literature method, the results of this study show that gender inequality, which is deeply rooted in social relations, has an impact on various aspects of society, including education and the labor market, underlining the importance of addressing cultural and social factors to increase women's participation in economic development. A multidisciplinary approach is essential in understanding and addressing gender inequality, considering economic and sociological influences to achieve a more holistic view of the issue.